ENABLERS OF BANK CREDIT FLOW TO AGRO-PROCESSING SMEs: THE ROLE OF BANK CREDIT TRANSPARENCY IN TANZANIA - Justus Mwemezi; Abdelhak Senadjki; Lau Lin Sea, (Malaysian Journal of Business and Economics (MJBE), 2023)
This research aimed to determine how bank credit transparency increases the flow of loans by mediating the relationship between credit risk management and credit flow to agro-processing SMEs. Since previous studies favored demand-side transparency, this study aims to fill the research gap by investigating the supply side. Information was gathered using the survey method. 397 Tanzanian bank branches were approached and asked to complete the questionnaire. Partial least square structural equation modeling (PLS-SEM) was applied to analyze the data. The empirical data revealed that information asymmetry and credit risk management negatively influence bank loan flow. Institutional lending structures had a significantly positive effect on bank credit flow. Policymakers and practitioners can use the findings of this study to improve bank credit transparency to borrowers and for the sustainability of agro-processing SMEs.